2011
DOI: 10.1007/s10611-011-9309-2
|View full text |Cite
|
Sign up to set email alerts
|

Guardianship for crime prevention: a critical review of the literature

Abstract: Cohen and Felson's (Cohen and Felson American Sociological Review 44 (4):588-608, 1979) routine activity theory posits that for a crime to occur three necessary elements must converge in time and space: motivated offenders, suitable targets, and the absence of capable guardianship. Capable guardians can serve as a key actor in the crime event model; one who can disrupt, either directly or indirectly, the interaction between a motivated offender and a suitable target. This article critically reviews the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 41 publications
1
130
0
Order By: Relevance
“…Hollis-Peel et al [18] found that although there has been substantial research on routine activities theory, the guardianship component of the theory has been largely ignored. Felson (in [16]: 53) describes guardianship as being exercised by those who serve "by simple presence to prevent crime and by absence to make crime more likely."…”
Section: Introductionmentioning
confidence: 99%
“…Hollis-Peel et al [18] found that although there has been substantial research on routine activities theory, the guardianship component of the theory has been largely ignored. Felson (in [16]: 53) describes guardianship as being exercised by those who serve "by simple presence to prevent crime and by absence to make crime more likely."…”
Section: Introductionmentioning
confidence: 99%
“…Rangers are not the only capable guardians; informal guardians can also prevent a criminal act from happening (Brown and Altman 1982;Hollis-Peel et al 2011). In this study's context this includes private landowners and tourist operators, who are capable of reporting suspicious Fig.…”
Section: Minimize Riskmentioning
confidence: 99%
“…For example, Hollis-Peel et al, in a literature review of the guardian figure in routine activity theory, have defined guardianship as "the physical or symbolic presence of an individual (or group of individuals) that acts (either intentionally or unintentionally) to deter a potential criminal event" (Hollis-Peel, Reynald, van Bavel, Elffers, & Welsh, 2011, p. 54), a definition that includes elements that they view as insufficiently specified in the original article by Cohen and Felson (1979) as well as later works. One example is closed-circuit television (CCTV), which is operated by people whose presence at the crime site is not physical (Hollis-Peel et al, 2011). Felson himself, in an effort to tie his theory to Hirschi's social control theory (1969), refines the figure of the guardian, distinguishing the "intimate handler" from the "place manager" (Felson, 1995).…”
mentioning
confidence: 99%